Urea dosing by urease - Velásquez, Manuel A. (1918)
Beside the dosing methods urea based on the action of nitrous acid, hypochlorites or hípobremitos, other methods based on the properties of some bacteria (Micrococcus Urae) of decomposing carbon dioxide and urea ammonia, by urine, placed at room temperature, serves as a culture medium in which the bacteria grow. However, the same decomposition into carbon dioxide and ammonia can be obtained by boiling with alkali or by heating for several hours at 150 ° urea with acids.